Bowen’s Disease of the Nipple and Areola: Case Report and Literature Review - Zhang G; Lu Y; Liu B; Wang Y; Li W; Xu Y (Dove Medical Press, 2023)
Guiyun Zhang,1 Yufeng Lu,2 Bin Liu,3 Yanmei Wang,4 Wenyi Li,1 Yangchun Xu1 1Department of Dermatology, The Second Hospital of Jilin University, Changchun, 130041, People's Republic of China; 2Department of Thoracic Surgery, China-Japan Union Hospital of Jilin University, Changchun, 130000, People's Republic of China; 3Department of Breast Surgery, The Second Hospital of Jilin University, Changchun, 130041, People's Republic of China; 4Department of Clinical Nutrition, Jilin Province People's Hospital, Changchun, 130021, People's Republic of ChinaCorrespondence: Yangchun Xu, Department of Dermatology, The Second Hospital of Jilin University, No. 218 Ziqiang Street, Nanguan District, Changchun, 130041, People's Republic of China, Tel +86-431-8113-6244, Email xuyc@jlu.edu.cnIntroduction: Bowen's disease (BD) commonly occurs in sites of chronic sunlight exposure such as head, neck and extremities. It rarely distributes on the nipple and areola.Case Presentation: A 59-year-old female presented with crusted plaque on the right breast for over 1 month. Physical examination found an asymptomatic plaque (5 cm × 5 cm) with irregular shape on the right breast. Histopathological examination suggested irregularly acanthotic epidermis and atypical epidermal cells. Dermis showed inflammatory cell infiltration. Immunohistochemical staining showed negative staining for cytokeratin 7 and cytokeratin 20, and positive staining for Ki67 (60%). The mass was excised and no recurrence occurred in the follow-up. Additionally, we reviewed the literature about BD of the breast and summarized the clinical manifestations, histological features, and treatment options.Conclusion: We reported a rare BD case involving nipple and areola. Wide local excision and complete nipple excision are effective for patients with BD of the nipple and areola.Keywords: Bowen's disease, breast, nipple, case report